Preliminary analysis of the relationship between the exercise and consumption of probiotics: A look at the Costa Rican consumer - Aguirre González, Juan Antonio (2015)
The study analyzes the consumption of probiotics and exercise. The sample was intentional and a profile of the consumer and ordinal logistic equation were developed. The variables that explain the frequency of exercise are: education, level of consumption of probiotics, activities undertaken to exercise, usage of the media for information, age and place of residence. The hypothesis proposed is accepted as preliminarily, given the relative importance in the frequency of exercise that consumption of probiotics occupies in the equation.